(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2026)
The aim of this research was to analyze the psychology unit prescribed in philosophy and humanities textbooks for secondary stage classes (10th grade,11th grade literary stream,12th grade literary stream ) According to the Indicators of the theory of multiple intelligences. To achieve this goal, a descriptive-analytical approach was used through content analysis. A list of multiple intelligence indicators was prepared, including the seven intelligences (linguistic, logical, visual, bodily, musical, social, and interpersonal). This was used to analyze the psychology unit from the philosophy textbook for the three grades. The necessary validity and reliability were tested. To extract results, frequencies, percentages, and the Chi-square test(x2) were used for goodness of fit. The results of the analysis were as follows: The distribution of multiple intelligences in the psychology unit for the three grades was unequal, as the intelligences (visual, linguistic, and interpersonal) were included in order, with higher scores than the expected frequency for the 10th grade. In the 11th grade, the intelligences (logical, interpersonal, visual, and linguistic) emerged, in order, with higher scores. In the 12th grade, the intelligences (interpersonal, visual, logical, and social) were more frequently than expected, and the inclusion of bodily-kinesthetic and musical intelligences was very low. In light of the results, some recommendations and proposals were presented, including reconsidering the development of secondary stage curricula and designing them according to the theory of multiple intelligences